CO2 adsorption at variable temperatures using clays from Ecuador. Potential uses in the cement industry - Játiva Quishpe, Nelson Dario (2024)
The present study proposes using Ecuadorian clays that are beneficial for encapsulating or adsorbing (liquid or gaseous) CO2 particles or other low molecular weight substances, aiming to develop new techniques for caring for the environment. For this reason, the synthesis and characterization of Ecuadorian clays extracted from different provinces and available in the Chemistry laboratory of Yachay University has been carried out, taking advantage of the existing infrastructure and equipment (high pressure reactors, X-ray diffractometer, centrifuges, ovens and furnaces), which are suitable for this type of applications. In addition, these treatments must guarantee efficient adsorption at different temperatures and pressures, accompanied by an exhaustive comparison with similar processes described in the scientific literature. Given that the capture of carbon dioxide CO2 is a priority for the care of the environment, the justification of this project would be the development of a material that is a good adsorbent that is easy to install and is applicable in the industrial sector such as the cement industry, this material could be an innovative and effective solution to reduce emissions and improve CO2 capture techniques.